Prediction of clinical outcomes in Crohn's disease by using confocal laser endomicroscopy: results from a prospective multicenter study - Tontini, Gian Eugenio; Mudter, Jonas; Günther, Claudia; Milani, Valentina; Atreya, Raja; Rath, Timo; Nagel, Andreas; Hatem, Giorgia; Sturniolo, Giacomo Carlo; Vecchi, Maurizio; Neurath, Markus; Galle, Peter R.; et al. (Gastrointestinal Endoscopy, 2018)
BACKGROUND AND AIMS: Assessment of prognostic factors in patients with Crohn's disease (CD) is of pivotal importance for early intervention and "treat-to-target" strategies. Confocal laser endomicroscopy (CLE) enables on-demand in vivo characterization of mucosal inflammatory and architectural changes during endoscopy. We prospectively assessed the value of CLE for prediction of clinical outcome parameters in CD. METHODS: Consecutive patients with CD undergoing colonoscopy were included in a multicenter study. Confocal imaging focused on 2 highly reproducible histologic hallmarks of active colonic inflammation: focal cryptitis and crypt architectural abnormality. We evaluated whether CLE, CD endoscopic index of severity (CDEIS), serum C-reactive protein (CRP), and CD activity index (CDAI) were associated with the risk of medical treatment escalation, transmural adverse events, and CD-related hospitalization or surgery during a 4-year follow-up. RESULTS: Among 49 patients (53% men, median age, 39 years), baseline CRP was ≥5 mg/L in 47%, CDEIS ≥3 in 75%, and CDAI >150 in 51%. Focal cryptitis and crypt architectural abnormality were observed in 63% (CLE+ group). CLE+ patients showed an increased incidence of medical treatment escalation (P < .001; relative risk [RR] = 3.27) and transmural lesions (P = .025; RR = 1.70), whereas patients with CRP ≥5 mg/L had increased CD-related hospitalization and surgery (P = .020, RR = 2.71) at 1-year follow-up. No further association with prognostic clinical outcomes was found over the 1-year follow-up as well as for CDEIS and CDAI at any time. CONCLUSIONS: CLE reveals CD-related features of mucosal inflammation and allows for early prediction of relevant clinical outcomes. Further studies should now address whether this promising prognostic tool could refine the timing of treatment strategies in patients with CD.
EVALuna2:35166